(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Annotation: This article discusses the relevance of the use of modern Internet technologies in the teaching of foreign languages and also analyzes the importance and effectiveness of the use of web technologies in the study of foreign languages both in class and in the independent work of students. The author analyzes different points of view on the expediency of using information technology in the teaching of foreign language and expresses a comprehensive position on this issue, supported by illustrative examples of the positive effect of using modern technology. The author believes that using web resources, teachers greatly simplify the process of communication of students both among themselves and with native speakers, as students are able to communicate both in writing and orally through video conferences or social networks, and not only on the subject matter but discovering situations of daily communication, as close to real-life communication as possible.